RECURRENT PREGNANCY LOSS AND ASSOCIATION OF MTHFR, PAI-1 AND ACE GENE POLYMORPHISMS IN WOMEN - Pandey, Snehlata; Pandey, Archana; Chauhan, U.K.; Tripathi, Arvind; Tripathi, Jitendra; Dubey, Sanjeev; Deo Saket, Rishabh (International Journal of Clinical and Biomedical Research, 2015)
Recurrent pregnancy loss (RPL) is a significant clinical problem that may occur before the 20th week of gestation. There is no general consensus on how many consecutive abortions are considered as RPL. The goal of this study is to investigate the correlation between recurrent miscarriage (RM) and common polymorphisms in angiotensin-converting enzyme (ACE), plasminogen activator inhibitor 1 (PAI-1) and Methylenetetrahydrofolate Reductase (MTHFR) genes among women experiencing RM. The literature existing in different population was searched and based on these finding we conclude that polymorphism in either one of these genes may increase chances of miscarriage. KEYWORDS: Polymorphism; Recurrent pregnancy; Plasminogen activator inhibitor 1.